Panel Data Regression Analysis on Factors Affecting Firm Value in Manufacturing Companies - Trisnadi Wijaya (Journal of Applied Business, Taxation and Economics Research, 2022)
The shareholders' wealth can increase when the company's value increases, which is indicated by the rise in share prices on the stock exchange. This research aims to analyze the factors that influence firm value. Samples were taken using the purposive sampling method and obtained from a selection of 70 manufacturing companies. Data analysis used the panel data regression method, which was processed with EViews 10 program. The Random Effect Model was chosen as the correct model for this research. The research results show that the Current Ratio and Debt to Equity Ratio have no significant effect on firm value. In contrast, firm size and Return on Equity significantly affect firm value.